Analysis of 5-Methylcytosine Regulators and DNA Methylation-Driven Genes in Colon Cancer - Du, Cheng; Liu, XinLi; Li, Mingwei; Zhao, Yi; Li, Jie; Wen, Zhikang; Liu, Min; Yang, Meina; Fu, Boshi; Wei, Minjie (Frontiers in Cell and Developmental Biology, 2022)
Abstract Background: Epigenetic-driven events are an important molecular mechanism of carcinogenesis. The methylation status of genes could be regulated by the 5-methylcytosine (5mC) regulators. The interaction among 5mC regulators, their impact on DNA methylation-driven genes, and oncogenic pathways remain unclear in colon cancer (CC). And the clinical value of such epigenetic-driven events needs further research. Methods: The transcriptome and epigenetic data were obtained from the TCGA dataset. The oncogenic pathways adjusted by 5mC regulators were identified by the Gene Set Variation Analysis (GSVA). Spearman Correlation Coefficient (SCC) between 5mC regulators or transcription factors (TFs) and shortlisted genes was calculated. The differential expression genes (DEGs) of DNA methylation-driven genes were identified by the “edgeR” and “methylmix” package. Those genes related to diagnosis were defined as shortlisted genes after observation of expression level in extracellular vesicles (EVs) and histology. And the risk signature was validated by the ROC curve. Results: MYC targets pathway and PI3K-AKT-mTOR signaling pathway were identified as the hallmark-related pathways associated with 5mC regulators. And P53 pathway was subject to the influence of regulators’ expression. A five methylation-driven gene signature (FIRRE, MYBL2, TGFBI, AXIN2, and SLC35D3) was developed as the biomarker for CC diagnosis. Meanwhile, those genes positively related to 5mC regulators and interacted with their relevant TFs. Conclusions: In general, 5mC regulators are positively related to each other and DNA methylation-driven genes, with the relationship of multiple active and inhibitory pathways related to cancer. Meanwhile, the signature (FIRRE, MYBL2, TGFBI, AXIN2, and SLC35D3) can prefigure prospective diagnosis in CC.